How to make urban renewal sustainable? Pathway analysis based on fuzzy-set qualitative comparative analysis (fsQCA) - Huang, Yijing; Wei, Wanyue; Ferreira, Fernando A. F. (International Journal of Strategic Property Management, 2023)
Even though urban renewal has attracted much attention in recent years, relatively few studies focus on the sustainability of urban renewal projects, which is surprising given the associated economic benefits. To fill this gap, we review 31 typical cases of urban renewal in China that have existed for over 10 years and utilize fuzzy set qualitative comparative analysis (fsQCA) to identify causal configurations that lead to a high level of stakeholder satisfaction. Our findings show that: (1) there are four antecedent configurations that lead to the sustainability of urban renewal of urban renewal (these are: ~ preservation of history and culture * differentiation * project reformation * ~ incremental innovation; ~ preservation of history and culture * differentiation * commercial publicity * incremental innovation; preservation of history and culture * commercial publicity * ~ project reformation * incremental innovation; and preservation of history and culture * differentiation * ~ commercial publicity * project reformation * incremental innovation); (2) compared with other conditions, differentiation and incremental innovation play more important roles in the sustainability of urban renewal; and (3) not only the improvement of the environment but also the operation and management of projects should be considered carefully. This paper contributes to urban renewal literature and offers practical suggestions for sustainable urban development.